Pinggan Kalori (PIKA V1) / Muhammad Syakir Suhaimi, Siti Maisarah Abu Bakar and Haira Azura Talip - Suhaimi, Muhammad Syakir; Abu Bakar, Siti Maisarah; Talip, Haira Azura (2021)
Platec Enterprise introduced a technology called PIKA V.1 which is a plate that helps you to automatically weigh calories of each meal precisely and it is very useful for people who want to consuming a well-balanced diet. The purpose of this product is to make it easier for people to count food calories without using charts to find food calories. Furthermore, since people nowadays are too busy to do exercise or physical activity this product can help with reduce calories intake. Also, our business will be capable of making profit and expensing our business and contribute to awareness of the importance of eating balanced diet. This product is added to its characteristics into a technological plate with elegant hardware which is to calculate the calories of food precisely. Our target market is for obese people or people who want to lose their weight, those who want to practice a healthy lifestyle and also athletes who want to control energy intake. The competitive of our product are SmartPlate, MyFitnessPals, Lose It! and General Electric (GE) Easy Cal. The advantages that all our competitors have in our products yet we use technology that can calculate food calories accurately and without counting manually. By selling the product with the price of RM145.00 per unit we shall expected to gain the profit of RM178,920,00.00 when selling it to 22,365,000 our target customer in Malaysia. The profit was gain after deducting the cost price of RM65.00 per unit. Platec Enterprise have set up an organization that consist of the Director, Project Manager, Sales Leader, Marketing Head, Financial Advisor and Quality Manager. This management team is effective in controlling and expensing our product.